Maḫbär et sänbäte: associations religieuses en Ethiopie - Ancel, Stéphane (Aethiopica, 2005)
Faithful of the Ethiopian Orthodox Täwaḥǝdo Church gather sometimes into a religious association. We can distinguish two types of religious associations: the maḫbär and the sänbäte. These two types are organized on the same scheme and are led by the faithful themselves. Both are based on a fundamental concept, which is to gather faithful around a banquet for a commemoration. Maḫbär and sänbäte are a representation of a zǝkǝr, a crucial concept in the Ethiopian Christianity. The religious authority is shared by one priest who leads the liturgy of the ritual. The presence of a priest without an organizational role highlights the influence of the laymen to organize their own religious life outwards the cast-iron ecclesiastical organisation. The social and religious influence of these organizations is very important in towns and in the countryside. To be member of these associations is a sign of an important social status in the parish community and the reality of both maḫbär and sänbäte shows the existence of a way of dialogue between the Church and the faithful.